Reducing Aggressive Behavior X Through Deaf Child Allowance Shortly Elimination Procedure (Time-Out) (Single Subject Design Class II.B in SLB Muhammadiyah Pauh IX Padang) - Herda Aulia (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstrack: This research was conducted as a student with moderat hearing losses got obstacles behavior disorder. She likes to hit friend, teacher, and others who made his angry. Purpose of this study is to prove the preliminary procedure can reduce aggressive behavior shortly (hit) in child with hearing X. This was a single subject design which used A-B-A design. Technique analysis of data using visual analysis graphs. The results show the baseline condition (A1) observations were made as much as nine times which range 9-19, the intervention condition as much as 12 times the range of 3-10 and on baseline conditions (A2) as much as 5 times which range 2-4. Overlap data on to baseline conditions (A1) and intervention is 0%, and the overlap data on to baseline (A2) and the intervention is 0%. The results of data analysis show decrease. It can be concluded shortly elimination procedure (time-out) can reduce aggressive behavior deaf children X. It is recommended that teachers can use shortly elimination procedure (time-out) in addressing child behavior disorders. Kata kunci: Mengurangi Perilaku Agresif, Prosedur Penyisihan Sesaat (Time Out) , Anak Tunarungu.